2011
DOI: 10.1007/s11434-011-4372-8
|View full text |Cite
|
Sign up to set email alerts
|

Coral reef ecosystems in the South China Sea as a source of atmospheric CO2 in summer

Abstract: during the summers of 2008 and 2009 revealed that both air and surface seawater partial pressures of CO 2 (pCO 2 ) showed regular diurnal cycles. Minimum values occurred in the evening and maximum values in the morning. Air pCO 2 in each of the three study areas showed small diurnal variations, while large diurnal variations were observed in seawater pCO 2 . The diurnal variation amplitude of seawater pCO 2 was ~70 μmol mol -1 at the Yongshu Reef lagoon, 420-619 μmol mol -1 on the Yongxing Island reef flat, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Our result, however, indicated that the enhanced PP in winter has a stronger influence to draw down the seawater 12 CO 2 than the influx of the DIC with lower δ 13 C values associated with the vertical mixing at our study site. This interpretation is further supported by the field surveys on the coral reef systems in the NSCS, which suggested that the seawater carbonate chemistry of the coral reef was primarily controlled by biological processes (Chen et al, ; Dai et al, ; Yan et al, , ). These results suggest that the decadal variability of the coral ∆ δ 13 C can be used as a reliable proxy for the PP in the NSCS.…”
Section: Resultsmentioning
confidence: 78%
“…Our result, however, indicated that the enhanced PP in winter has a stronger influence to draw down the seawater 12 CO 2 than the influx of the DIC with lower δ 13 C values associated with the vertical mixing at our study site. This interpretation is further supported by the field surveys on the coral reef systems in the NSCS, which suggested that the seawater carbonate chemistry of the coral reef was primarily controlled by biological processes (Chen et al, ; Dai et al, ; Yan et al, , ). These results suggest that the decadal variability of the coral ∆ δ 13 C can be used as a reliable proxy for the PP in the NSCS.…”
Section: Resultsmentioning
confidence: 78%
“…These results made clear that photosynthesis/respiration caused the major changes of p CO 2 between different seasons. These results also support those obtained in Yongxing and Yongshu Reef (∼1:1.6, ∼1:3.3) [ Yan et al ., ], which are much higher than the ratio of the SCS basin (∼1:14) [ Cao et al ., ], suggesting CaCO 3 production is much more prominent in the coral reef system. The Luhuitou fringing reef flat may therefore function as other typical coral systems in terms of the metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Observed results, e.g., ∼0.4 mmol C m −2 d −1 at Yongshu reef and ∼4.7 mmol C m −2 d −1 at Yongxing reef of SCS by Yan et al . [], showed that these two reefs act as sources of atmospheric CO 2 in summer. The Yongxing reef acts as a weak source of atmospheric CO 2 at ∼1.48 mmol C m −2 d −1 in winter [ Dai et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regionally averaged primary production and sea surface chlorophyll concentrations vary within limited ranges (Tan and Shi, 2009;Sasai et al, 2013). On the other hand, due to abundant coral reefs on Nansha, Xisha, and Zhongsha islands, this domain was potentially influenced by CaCO 3 formation, which releases CO 2 into the atmosphere Yan et al, 2011). Domain D was located between 18 and 21 • N and 118 and 121 • E, where the Kuroshio intrusions generate mesoscale cyclonic eddies in the northeast monsoon season (Sheu et al, 2010a) and thus induce pumping/entrainment of nutrients and CO 2 from the depths (e.g., Xu et al, 2009;Shang et al, 2012;Sasai et al, 2013).…”
Section: Study Areamentioning
confidence: 99%